Coming out Through an Intersectional Perspective: Narratives of Bisexuality and Polyamory in Italy. Issue 1 (2nd January 2018) - Gusmano, Beatrice
ABSTRACT: Through an intersectional perspective, the author analyzes what it means to perform a bisexual and polyamorous identity in the Italian familistic welfare regime. Considering the intersections of polyamory and bisexuality, the author employs the Greimas semiotic square to read the process of coming out experienced by people who shared their experiences on polyamory: two interviewees define themselves as bisexual ciswomen, and one self-defines as a transsexual gay man in a primary relationship with a self-defined bisexual cisman. Afterwards, the author explores how they live their intimate lives through compulsory invisibility, coming out, and staying invisible. Finally, the author focuses on how the existence of non-normative communities opens up the possibility of meeting other bisexual people in a context where there are no bisexual communitie, and argues that this process allows people to self-identify as bisexual and polyamorous in the public sphere.